Review of Choman Hardi’s Gendered Experiences of Genocide: Anfal Survivors in Kurdistan-Iraq - Avramopoulou, Eirini (Historein, 2013)
Review of Choman Hardi, Gendered Experiences of Genocide: Anfal Survivors in Kurdistan-Iraq, Farnham: Ashgate, 2010. xii + 217pp